Изучение антиоксидантной активности некоторых пентациклических тритерпеноидов; Тенденции развития науки и образования в области естественнонаучных дисциплин - Воронова О. А. Олеся Александровна; Плотников Е. В. Евгений Владимирович; Калиева С. С.; Нурпейис Е. Е.; Мамаева Е. А. Елена Андреевна; Ташенов А. К.; Бакибаев А. А. Абдигали Абдиманапович (2016, 2016)
It was studied the antioxidant activity of a number of pcntacyclic triterpenoids using the method of cathodic voltamperometry and oxygen electrochemical reduction process. It is shown that bctulin diacetate exhibits more pronounced antioxidant activity compared with samples of betulin or allobctulin due to the fact that the double bond in isopropenyl moiety of betulin diacetate serves as the active site of oxidation.